Combination of Hybrid CVD and Cation Exchange for Upscaling Cs‐Substituted Mixed Cation Perovskite Solar Cells with High Efficiency and Stability. (22nd November 2017) - Jiang, Yan; Leyden, Matthew R.; Qiu, Longbin; Wang, Shenghao; Ono, Luis K.; Wu, Zhifang; Juarez‐Perez, Emilio J.; Qi, Yabing
Abstract: Mixed cation hybrid perovskites such as Cs x FA1− x PbI3 are promising materials for solar cell applications, due to their excellent photoelectronic properties and improved stability. Although power conversion efficiencies (PCEs) as high as 18.16% have been reported, devices are mostly processed by the anti‐solvent method, which is difficult for further scaling‐up. Here, a method to fabricate Cs x FA1− x PbI3 by performing Cs cation exchange on hybrid chemical vapor deposition grown FAPbI3 with the Cs + ratio adjustable from 0 to 24% is reported. The champion perovskite module based on Cs0.07 FA0.93 PbI3 with an active area of 12.0 cm 2 shows a module PCE of 14.6% and PCE loss/area of 0.17% cm −2, demonstrating the significant advantage of this method toward scaling‐up. This in‐depth study shows that when the perovskite films prepared by this method contain 6.6% Cs + in bulk and 15.0% at the surface, that is, Cs0.07 FA0.93 PbI3, solar cell devices show not only significantly increased PCEs but also substantially improved stability, due to favorable energy level alignment with TiO2 electron transport layer and spiro‐MeOTAD hole transport layer, increased grain size, and improved perovskite phase stability. Abstract : Cs‐substituted mixed perovskite modules are prepared by a new developed large‐area‐compatible method combining hybrid chemical vapor deposition and cation exchange. Power conversion efficiency (PCE) as high as 14.6% is achieved, benefiting from the large‐area film uniformity on macroscopic and microscopic scales. In‐depth study shows that 7% Cs + in Cs x FA1− x PbI3 is the optimal ratio for achieving best device PCE and longest lifetime.